2013
DOI: 10.1021/ac4005887
|View full text |Cite
|
Sign up to set email alerts
|

Automated Capillary Electrophoresis System for Fast Single-Cell Analysis

Abstract: Capillary electrophoresis (CE) is a promising technique for single-cell analysis, but its use in biological studies has been limited by low throughput. This paper presents an automated platform employing microfabricated cell traps and a three-channel system for rapid buffer exchange for fast single-cell CE. Cells loaded with fluorescein and Oregon green were analyzed at a throughput of 3.5 cells/min with a resolution of 2.3 ± 0.6 for the fluorescein and Oregon green. Cellular protein kinase B (PKB) activity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 36 publications
3
74
1
Order By: Relevance
“…The three-channel system for physiologic buffer, air, and electrophoretic buffer was fabricated from PDMS (Figure S1 Electronic Supplementary Material) [33]. The channel for loading electrophoretic buffer was 3 cm in length, 0.5 cm in width, and 1.5 mm in depth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three-channel system for physiologic buffer, air, and electrophoretic buffer was fabricated from PDMS (Figure S1 Electronic Supplementary Material) [33]. The channel for loading electrophoretic buffer was 3 cm in length, 0.5 cm in width, and 1.5 mm in depth.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were lysed by adding 10 μL methanol and stored at −80°C until analysis. Lysate samples were diluted in electrophoretic buffer (27 mM monosodium phosphate and 10% 1-propanol at pH 7.3) and analyzed using a custom-built CE system, described previously [33]. The sample was separated in a 35 cm fused-silica capillary with an inner diameter of 30 μm.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a chip containing a channel system and a cell trap was fabricated that allowed transfer the content of a single trapped cell after lysis into a separation capillary [117][118][119]. The cells were lysed by a laser pulse and the content was injected electrokinetically into a 35 cm, 30 μm id, fusedsilica capillary.…”
Section: In-capillary Enzyme Assaysmentioning
confidence: 99%
“…This research encourages the use of different platforms that can isolate and assay the cells individually. Zarrine-Afsar and Krylov 6 and Dickinson et al 4 have previously reported capillary electrophoresis-based methods to monitor the activation of protein kinase A (PKA) and protein kinase B (PKB) in single cells. However, these methods involve either the cloning of cells to transiently express the GFP-tagged protein substrate or the use of immunofluorescence antibody staining to monitor kinase activity in trapped single cells.…”
Section: -1058/2014/8(3)/034104/9mentioning
confidence: 99%
“…The capillary electrophoresis system was automatized to analyze $3.5 cells/min. [4][5][6][7][8][9][10] Compared with these methods, the droplet based technology is attractive [11][12][13][14][15][16][17][18][19][20][21] because of its ultra high throughput cell encapsulations ($1000 droplets/s) [22][23][24] and accurate fluidic controls. Accordingly, a wide range of droplet base single cell polymerase chain reactions (PCR) were carried out in previous studies.…”
mentioning
confidence: 99%